The Discourse Dimensions of Hoax News in Online Media During the COVID-19 Pandemic - Hasbi Sofan Zain; Zamzani Zamzani (MASI Mandiri Edukasi, 2026)
This research aims to explain how hoax news was constructed and disseminated during the COVID-19 pandemic by applying Critical Discourse Analysis (CDA) to three dimensions: (1) textual, (2) discourse practice, and (3) sociocultural practice within online media. The research uses a descriptive qualitative approach, with data sourced from hoax news labeled “Hoax” by Kominfo that had not been deleted. The data were analyzed using Norman Fairclough’s (1989) three-dimensional model of discourse analysis. The results show that: (1) The textual dimension of hoax news during the pandemic is constructed through cohesion and coherence, grammar, and diction. (2) The discourse practice dimension includes the processes of text production, dissemination, and consumption in online media. (3) The sociocultural practice dimension operates at three levels: situational, institutional, and social. At the social level, many netizens expressed disappointment with the government, which was perceived as slow to respond to the COVID-19 threat, while others appreciated the policies implemented and even offered prayers for their success. This study concludes that linguistic features, production contexts, and the broader social dynamics of online communities influence the construction and spread of hoax news.